REVIEW STANDAR IAPI 2009 - Maya Indriastuti (Dinamika Akuntansi Keuangan dan Perbankan, 2012)
Public Accountants Professional Standards (SPAP) applicable in Indonesia during this refers tothe auditing standards of the Americans. The Code currently in force, namely adopting the IFACis comprised of two parts namely Part A contains the Basic Principles of Professional Ethics andprovide conceptual framework for the application of principles, and Part B contains the Rules ofProfessional Ethics which provides illustrations of application of the conceptual framework incertain situations.Some differences between the draft Code of Conduct Code of Conduct with thePublic Accountants that currently applies, among others: 1) The number of paragraphs 2) Thecontents of the draft Code of Conduct 3) Application of Conceptual Framework. Besides the basicprinciples presented in Part A consists of five principles, namely Integrity, Objectivity,Competence and Professional Care, Confidentiality, and Professional Conduct. While the Codecurrently applies consists of eight principles, which are: Integrity, Objectivity, Competence andProfessional Care, Confidentiality, Professional Conduct, Professional Liability, Public Interest,and Professional Standards.Therefore the application of codes of conduct expected to be moreaccountable and transparent to the Profession of Public Accountants, Services provided by PublicAccountant wider than the old standard, and the more detailed sections and detailed that itsupports Public Accountants became more professional and increase public confidence.Key Words: public accountant professional standards, codes of ethics, accountability,transparency and public confidence